125k views
2 votes
Can someone answer this question?

Can someone answer this question?-example-1
User Matsolof
by
4.6k points

2 Answers

5 votes

Answer:

No solution.

Explanation:

(1/12)^-2b * 12^(-2b + 2) = 12

1/12 is basically the same thing as 12^-1.

12^(-1 * -2b) * 12^(-2b + 2) = 12

12^2b * 12^(-2b + 2) = 12

12^(2b - 2b + 2) = 12

12^2 = 12

Since the answers don't match up, the answer will be no solution.

Hope this helps!

User Coy
by
4.9k points
3 votes

Answer:

no solution

Explanation:

(1/12) ^ (-2b) + 12 ^(-2b+2) = 12

Rewriting 1/12 as 12 ^ -1

(12^ -1) ^ (-2b) + 12 ^(-2b+2) = 12

We know a^b^c = a^ ( b*c)

(12) ^ (-1*-2b) + 12 ^(-2b+2) = 12

(12) ^ (2b) + 12 ^(-2b+2) = 12

We know that a^ ( b+c) = a^ b * a^c

12 ^ 2b + 12 ^ -2b * 12 ^ 2 = 12

12 ^ 2b + 144 * 12 ^ -2b = 12

Let 12 ^ b = u

u^2 + 144/u^2 = 12

Multiply by u^2

u^4 +144 = 12u^2

Subtract 12 u^2

u^4 -12u^2 +144 =0

There is no real solution

User Lars Steen
by
4.4k points